Socialization of KOSJA Processing (Kompos Janjang Kosong) in Oil Palm Farmer Groups in Buatan Baru Village, Siak Regency, Riau Province: Sosialisasi Pengolahan KOSJA (Kompos Janjang Kosong) pada Kelompok Tani Kelapa Sawit di Desa Buatan Baru Kabupaten Siak Provinsi Riau - Sutikno, Agus; Zamaya, Yelly; Putri, Vivin Jenika; Pramana, Angga; Rahmah, Anania; AR, Nur Hasnah; Hamzah, Anthony (Universitas Lancang Kuning, 2024)
As the area of oil palm plantations increases, the waste from oil palm empty fruit bunches also increases. By reducing the use of excessive chemicals, sustainable oil palm plantations can be achieved. One way to achieve this is by utilizing empty oil palm bunch waste into KOSJA (Kompos Janjang Kosong). This service aims to provide knowledge, understanding, and how to process empty oil palm bunches into KOSJA. This activity was carried out in Riau Province, Siak Regency, Kampung Buatan Baru, Kerinci Kanan District. The output achieved through this service is the increased understanding and knowledge of the community about the importance and benefits obtained from the utilization of empty palm bunch waste into KOSJA (Kompos Janjang Kosong).